Pelatihan Akuntansi Keuangan Kepada Petani Kopi Desa Karangpring Upaya Meningkatkan Kesejahteraan Masyarakat - Mubarok, Ahmad Faisal; Balasad, Rahyah Zahwa Ghamariah; Husna, Nadiyah Nurul; Febrian, Ciko Edo; Hibatullah, Reihan Wudd; Sayekti, Yosefa; Aziz, Nur Kholik (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Financial Accounting Training provided to coffee farmers in Karangpring Village aims to improve community welfare through a better understanding of financial recording. This program is designed to help farmers understand the importance of proper bookkeeping, so they can manage their coffee business more efficiently and accurately determine profits. This training was carried out with a socialization approach and direct practice in making simple financial reports. Evaluation of the effectiveness of the training is carried out through pretests and posttests which measure the increase in participants' understanding of the material being taught. The evaluation results show that this training was successful in increasing the farmers' ability to apply accounting principles, which is expected to have a positive impact on their welfare.